Analisis Pengaruh Bauran Pemasaran Terhadap keputusan Pembelian - Richard Berlien; Sumaizar Sumaizar; Satria Sinambela (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2019)
Tea Powder is a delicious beverage powder in Sidamanik. In developing the business, the company will expand the sales area in each sub district. The company chooses the low end segment, which is considered to be at low cost, and determines product positioning only in the sweet bread market. Management has conducted the marketing mix strategy. But, the effectiveness is still being argued, especially regarding the problems of the expansion of sales area. Thus, the scientifically conducted study is needed to measure the marketing mix and its influence on the decision, statisfaction, and the loyalty of customers. Results of the study showed that the overall hypothesis were acceptable and there were significant influences of the product, distribution, and promotion on consumers’ decison; there were significant influences of product and price on consumers’ satisfaction; there were significant influences of consumers’ decision on consumers’ satisfaction and loyalty, and there was a significant influence of consumers’ satisfaction on consumers’ loyalty.